Long COVID in pediatric age: an observational, prospective, longitudinal, multicenter study in Italy - Esposito, Susanna; Puntoni, Matteo; Deolmi, Michela; Ramundo, Greta; Maglietta, Giuseppe; Poeta, Marco; Zampogna, Stefania; Colomba, Claudia; Suppiej, Agnese; Cardinale, Fabio; Bosis, Samantha; Castagnola, Elio; et al. (Frontiers in Immunology, 2025)
IntroductionThis observational prospective longitudinal multicenter study examines the occurrence and characteristics of long COVID (LC) in the Italian pediatric population.MethodsConducted across 12 Pediatric Units in Italy from January to March 2022, the study involved 1129 children diagnosed with SARS-CoV-2 infection. Data were collected via self-administered questionnaires at 1-3 months, 3-6 months, and 6-12 months post-infection, with LC defined as symptoms persisting for at least 2 months and occurring 3 months post-diagnosis.ResultsResults revealed that 68.6% of children reported at least one post-COVID symptom, with 16.2% experiencing LC. The most frequent symptoms included respiratory issues (43.4%), neurological and cognitive dysfunction (27.7%), gastrointestinal symptoms (22.1%), fatigue (21.6%), and sleep disturbances (18.8%). Age and gender differences were significant, with older children and females more prone to cardiovascular and neurological & cognitive dysfunction.DiscussionThe study highlights that LC in children presents similarly to adults, though less frequently. The occurrence of LC was lower compared to adult populations, likely due to the generally milder course of COVID-19 in children. The findings underscore the need for targeted follow-up and support for affected children, especially considering the long-term persistence of symptoms. Further research is necessary to explore the impact of COVID-19 vaccines on pediatric LC and the effects of different SARS-CoV-2 variants. These insights are crucial for developing strategies to manage and mitigate long-term impacts in children recovering from COVID-19.